KEANEKARAGAMAN TUMBUHAN OBAT DI BLOK PEMANFAATAN TAMAN WISATA ALAM BIPOLO, DESA BIPOLO, KECAMATAN SULAMU, KABUPATEN KUPANG, PROVINSI NUSA TENGGARA TIMUR - Stevania Evangelin Leki; Mamie E Pelondo'u; Astin E Mau (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2020)
Indonesia has various types of flora and many unique varieties of tropical plants. There are about 8000 species of medicinal plants spotted, however only around 800 to 1200 species that have been used as traditional medicinal herbs or jamu. First thing to do before publishing the benefits of medicinal plants is to determine its level of diversity in an area. The introductionof medicinal plants in science can be used as information for making traditional medicinal ingredients that are useful for the community, one of which is the community around the BipoloNature Park. This research aims to determine levels of diversity and to specify medicinal plants that have been used by locals at Utilization Bloc in Bipolo Nature Park. Data collection techniques are done by deploying vegetation analysis, identifying medicinal plants, and by interviews. From the research conducted, diversity indices of medicinal plants measured by The Shannon diversity index (H') shows intermediate results for medicinal plants at Bipolo Park (1 ≤ H’ ≤ 3). Species richness measured by Margalef Index (R') shows low rank (R’ ≤ 5).Locals at utilization bloc in Bipolo Park utilize 21 species of medicinal plants that they get near by the place where they live. Leaf and bark are the most commonly used part of the plants with total up to 30%.